Analysis of Students’ Difficulties in Writing Recount Text at WR. Supratman 2 School - Vienya, Azzahra Tiara; Naisaburi, Tjut Zurie; Manik, Kresna Ningsih (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study aims to identify and examine the challenges students face when composing recount texts, focusing on the experiences of grade XI MIPA 2 students at WR. Supratman 2 School. A qualitative research approach was utilized, collecting data through interviews and written tests to gain a comprehensive understanding of the difficulties encountered by students. The analysis of the data revealed that grammar was the most significant area of struggle for the students. Many students exhibited difficulties with the proper use of tenses, sentence structure, and vocabulary, which impacted their ability to write coherent and accurate recount texts. Based on these findings, the study recommends that teachers place greater emphasis on teaching grammar in a more structured and gradual manner, ensuring that students have ample time to grasp the concepts fully. Teachers should consider adopting a slower pace and using diverse instructional strategies, such as interactive exercises and practical applications, to reinforce grammar rules and facilitate better understanding. Additionally, the study suggests that students engage in daily English practice, including writing, reading, and listening activities, to enhance their language skills over time. Regular practice can help students become more familiar with the language, improve their grammatical accuracy, and increase their confidence in using English both in and out of the classroom. By addressing these challenges through targeted teaching strategies and consistent practice, both teachers and students can work together to improve the overall quality of students' writing and their ability to effectively compose recount texts. The findings of this study highlight the importance of a focused approach to grammar instruction and encourage a more supportive learning environment for students developing their English language skills.